Maximizing Benefits From Punctual Ocean Infrastructure: An Ethical Perspective - Whoriskey, Frederick; Barbier, Michele; Mazur, Mackenzie; Hahn, Tobias; Kritzer, Jacob; Vallee, Richard (Frontiers in Marine Science, 2021)
Ethics are becoming a component of best practices in ocean science and observing systems, with the research community facing a duty to society to maximize the efficient use and benefits that stem from investments in ocean science/monitoring. Sustained ocean observing systems on issues of global importance are coordinated, internationally sanctioned and making the most out of the resources accorded to them and consequently fulfilling their duty to society. However, globally huge investments are made annually in establishing infrastructure for shorter-term, punctual studies that address targeted as opposed to broad science needs. More could be done to maximize the benefits and impacts of these punctual efforts. Given punctual infrastructure’s small and frequently transient nature, connections to enable sharing will probably be done locally, and both potential additional users and owners of the infrastructure will need to be energetic, receptive and flexible. The accommodation of new uses will have to be balanced against any costs of these additional activities, which could pose an ethical dilemma in themselves if they compromise the infrastructure’s ability to meet its original intent. However, such adaptive infrastructures may be the most efficient way to provide the resources needed to identify and monitor emerging or new ocean stressors.